Environmental History and the Concept of Agency: Improving Understanding of Local Conditions and Adaptations to Climate Change in Seven Coastal Communities. (1st October 2018) - Kennedy, Gregory; Raimonet, Mélanie; Berman, Matthew; Gaye, Ndickou; Huctin, Jean-Michel; Kaleekal, Thomson; Vanderlinden, Jean-Paul
Abstract : This article provides a synthesis of the results from seven global research sites working together to study adaptation to climate change in coastal communities under the moniker ARTISTICC (www.artisticc.net). It first aims to share these research results in order to demonstrate two general themes that emerge from our analysis and can help improve our understanding of community responses to environmental change broadly speaking. These themes are the continuity of environmental change and the legacy of colonialism. The goal is to demonstrate that comparisons across research sites are possible if an appropriate transdisciplinary framework is in place and also that environmental history is required to understand the past if we are to effectively tackle present conditions. Secondly, this paper offers reflections on the concepts of agency and adaptation and how the methodological divide between historians and social scientists can be further bridged to great benefit for all concerned. By being more reflective on our own disciplinary cultures, we can co-construct knowledge about how community cultures operate. The agency of local actors is central to understanding past choices and present obstacles to successful adaptation. Indeed, we must better appreciate the goals of local actors if we are to know what success looks like to them. Adaptation, whether adjustment or transformation, is often a long-term, complex process.